Improving Students’ Reading Comprehension on Descriptive Text Through Structured Note–Taking Strategy - Vina Regina; Juliana Juliana (Edumaspul: Jurnal Pendidikan, 2025)
This research aimed to improve the reading comprehension of tenth-grade students in understanding descriptive text by implementing the Structured Note-Taking Strategy at SMA Swasta Budi Agung Medan. The research employed Classroom Action Research (CAR), carried out in two cycles, each comprising the phases of planning, action, observation, and reflection. The participants included 35 students from class X Muhammad Hatta, who faced challenges in recognizing main idea, supporting details, and structuring essential information from the text. Data collection involved both quantitative and qualitative approaches. Quantitative data were gathered through multiple-choice comprehension tests, while qualitative data were obtained from observation sheets, interviews, documentation, and field notes. The results demonstrated consistent improvement over the two cycles, with the students’ average score rising from 50.86 in the pre-test to 74.71 after the first cycle, and further increasing to 86.85 following the second cycle. These findings indicate that the Structured Note-Taking Strategy effectively aided students in identifying and organizing key information within descriptive text. These results suggest that the Structured Note-Taking Strategy effectively supported students in identify and organize important information in descriptive text, This strategy is suggested for broader application in reading activities to further strengthen students’ comprehension.